The influence of foraging habitat on acoustic signal source levels in two bat species, Neoromicia capensis (Vespertilionidae) and Tadarida aegyptiaca (Molossidae) - Mutavhatsindi, Itani Victor (Department of Biological Sciences, 2018)
The source level of echolocation pulses is an essential parameter because it has an impact on the range at which bats perceive their environment and, most importantly, at which they detect prey. Echolocation pulse source level is under the control of the echolocator and its operational range is likely to vary with body size and foraging habitat because these determine the operational range needed by the bat. This study thus attempted to answer the following questions; (1) is the source levels of animal acoustic signals different in different situations? (2) Does body size and foraging habitat affect the source levels of animal acoustic signals? There are only a few studies that report on the source levels of echolocation pulses of free-ranging bats because of the difficulty of measuring the distance of the bat from the recording microphone. This distance is essential in calculating source levels of echolocation pulses. I used multiple microphone array system to investigate the echolocation sound signals, three-dimensional (3-D) acoustic flight paths and source levels of echolocation pulses at 10 cm standard reference distance from the mouth of a free-flying frequency-modulated (FM) bat, Neoromicia capensis and quasi-constant frequency (QCF) bat, Tadarida aegyptiaca. The two bat species differ in body size and foraging habitat. I found as predicted, that T. aegyptiaca, the larger of the two species and an open-air aerial hawker, emitted echolocation pulses of higher source levels and therefore had greater maximum detection distances than the smaller, clutter-edge aerial hawker, N. capensis. Tadarida aegyptiaca emitted echolocation pulses with an average of 146.9±4.6 (range 137.7 - 154.8) dB peSPL during emergence from the roost and an average of 143.0±4.9 (range 136.4 - 153.3) dB peSPL during foraging, extending the known range of free-flying bats. Neoromicia capensis emitted echolocation pulses with an average of 129.3±4.0 (range 119.3 - 138.7) dB peSPL during emergence from the roost and average of 132.8±5.0 (range 117.8 - 142.9) dB peSPL during foraging. As anticipated, I found N. capensis to be emitting echolocation pulses of higher source levels during foraging than when it emerged from the roost. However, there was no significant difference in the source levels of T. aegyptiaca between emergence from the roost and foraging habitat. The estimated maximum detection distances for the three insect size categories i.e. small, medium and large was greater for T. aegyptiaca than N. capensis. My data therefore suggests that bats might adjust their echolocation pulse source levels to suit their foraging habitat and situation.